SPEECH FUNCTION IN FEATURE STORIES IN READER’S DIGEST - Arta Rosaen; Lidiman Sinaga (State University of Medan, 2012)
This study is aimed to find out the dominant type and to explain the meaning of the Speech Functions used in Feature Stories of Reader’s Digest Magazines; The Council of Dads, Blind Optimism, and Where Children Sleep. The data were analyzed based on the 4 types of Speech Function suggested by Halliday (1994). The result shows that the most dominant type of Speech Function used in Reader’s Digest’ Feature Stories was statement which is realized by declarative mood. This indicate that the writer in order to deliver the ‘human interest’ to the readers, entertain the readers, describing the news hook to the reader, to narrated in a chronological the stories for the readers are by using Statements. Key words: Speech functions, feature stories.